2015
DOI: 10.1016/j.pbb.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine withdrawal in rats selectively bred for low (LoS) versus high (HiS) saccharin intake

Abstract: Cocaine use results in anhedonia during withdrawal, but it is not clear how this emotional state interacts with an individual's vulnerability for addiction. Rats selectively bred for high (HiS) or low (LoS) saccharin intake are a well-established model of drug abuse vulnerability, with HiS rats being more likely to consume sweets and drugs of abuse such as cocaine and heroin (Carroll et al. 2002) than LoS rats. This study examined whether the motivational consequences of cocaine withdrawal are differentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
2
6
1
Order By: Relevance
“…While differences between HiS and LoS rats were generally modest, the greater vulnerability in LoS rats, vs. HiS rats during both spontaneous and precipitated withdrawal agree with previous studies suggesting that the anhedonic effects of withdrawal may be more pronounced in the LoS line (Radke et al, 2014). These results contribute to our understanding of the interaction between sweet-preference and drug addiction.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While differences between HiS and LoS rats were generally modest, the greater vulnerability in LoS rats, vs. HiS rats during both spontaneous and precipitated withdrawal agree with previous studies suggesting that the anhedonic effects of withdrawal may be more pronounced in the LoS line (Radke et al, 2014). These results contribute to our understanding of the interaction between sweet-preference and drug addiction.…”
Section: Discussionsupporting
confidence: 89%
“…In these studies, in contrast to the greater sensitivity to the aversive effects of withdrawal measured using ICSS in the current study, LoS rats exhibited reduced spontaneous withdrawal-induced increases in the startle response following 7 days of morphine exposure, and reduced precipitated withdrawal-induced CPA following one exposure. The differences between this work and our recent studies (i.e., the present study and Radke et al, 2014) may be because different behavioral measures, such as ICSS, potentiated startle, and CPA, reflect different underlying emotional states and neural systems. For example, anhedonia as measured with ICSS is mediated by reduced responsiveness of the mesolimbic dopamine (reward) system, while anxiety as measured through startle is produced primarily through increased activity in extended amygdala (threat) circuitry (Lang et al, 2000; Nestler and Carlezon, 2006).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In previous studies of individual differences in drug seeking, results demonstrated differential responding to the positive and negative aspects of drug taking in HiS and LoS rats. While HiS rats exceeded LoS rats in drug intake (Perry et al, 2006, Anker et al, 2012) and reinstatement of drug-seeking behavior (Perry et al, 2006), LoS rats (vs. HiS) revealed greater reactivity to negative events, such as food restriction (Carroll et al, 2012) and withdrawal from ethanol (Dess et al, 2005), glucose (Yakavenko et al, 2011) morphine (Holtz et al, 2014b), and cocaine (Radke et al, 2014). Given the previous finding that lower drug-seeking animals respond more to negative aspects of drugs compared to higher drug-seeking animals, one potential explanation for the results that ALLO reduced reinstatement more in LoI than HiI rats is that these pharmacological manipulations produced more of a stress response in LoI rats compared to HiI rats.…”
Section: Discussionmentioning
confidence: 96%
“…For example, animals selected for low impulsivity (LoI vs. HiI), low saccharin intake (LoS vs. HiS), as well as adults (vs. adolescents), and males (vs. females) not only exhibit less drug seeking than their counterparts, but they also exhibit more sensitivity to punishment by histamine, greater signs of withdrawal from drugs of abuse, greater taste aversion, greater response to anxiogenic stimuli, and greater acoustic startle (Carroll et al, 2009; Carroll and Holtz, 2014; Holtz et al, 2013, 2014b; Holtz and Carroll, 2014; McLaughlin et al, 2011; Radke et al, 2014, but see Radke et al, 2013), while their counterparts (HiI, HiS, adolescents, and females, respectively) have greater response to positive aspects of drugs (i.e., greater drug-seeking and drug-taking behaviors, see review by Carroll et al, 2009). This raises the question of to what extent are individual differences in drug seeking understood based on differential reactions to positive or negative aspects of drugs.…”
Section: Introductionmentioning
confidence: 99%